ナルディライジンはT細胞を介して自己免疫性肝炎に関与する - 安藤, 朗; 平田, 多佳子; 西, 英一郎; 吉田, 晋也; 西, 清人; 里岡, 大樹; 大野, 美紀子 (日本薬理学会年会要旨集, 2023)
Autoimmune hepatitis (AIH) is a refractory inflammatory disease that causes progressive liver damage. While it has been suggested that regulatory T cells (Treg) have a significant role on the pathophysiology of AIH, the precise mechanism how AIH is controlled by Treg is still elusive.We have previously demonstrated that nardilysin (NRDC), a member of the M16 family of metalloendopeptidase, is involved in several inflammatory diseases (e.g. rheumatoid arthritis, non-alcoholic fatty liver) via the activation of TNF-α. NRDC was also reported to be involved in antigen processing, suggesting that NRDC in immune cells may play a significant role in the pathogenesis of autoimmune diseases including AIH.In this study, T cell-specific NRDC-deficient mice (CD4-CKO) and control mice (CONT) were intravenously injected with concanavalin A (ConA), which is a well-established model of acute AIH. Examination of liver histology and serum hepatic enzymes demonstrated that liver injury in CD4-CKO was significantly milder than that in CONT. Transcriptome analysis of splenic T cells revealed that the downstream genes of Foxp3, the master transcription factor of Tregs, were significantly altered in the CD4-CKO.Consistently, the number of liver-infiltrated Treg was significantly increased in CD4CKO compared with CONT. Finally, naïve T cells isolated from CD4-CKO differentiate into Tregs more efficiently in vitro compared with CONT. These findings suggest that NRDC controls the pathogenesis of AIH via Treg.